A study of the correlation between SCAT scores and scholastic achievement of third and fourth year high school students of Santa Isabel College - Centeno, Remedios R. (Animo Repository, 1970)
In this study the researcher intended to find out the adaptability of the Cooperative School and College Ability Test (SCAT) for use in a particular school, Santa Isabel College. This test, according to its authors, "aims to estimate the capacity Qf a student to undertake the academic work of the next higher level of schooling." Previous studies have proved that there is a fairly high correlation between SCAT scores end grade averages from the elementary grades to college.1 working en this hypothesis, the investigator proposed find out if the SCAT can be used as a predictor of future academic achievement as measured by the grade averages of the third and fourth year high school students of Santa Isabel College.